Arrows of the faithful: the importance of archery in Islam - Ngah, Nazlin Emieza; Adenan, Nur Dalila; Mohamad Azmin, Nur Azwani; Abdullah, Nasiha; Abd. Talib, Nurafida (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Here ore some examples: “Teach your children swimming, archery, and horse riding.' [Sunan Ibn Majah (3651)